Conceptual model of internet banking adoption with perceived risk and trust factors - Hammood, Waleed A.; Aminuddin, Afrig; Hammood, Omar A.; Abdullah, Khairul Hafezad; Sofyan, Davi; Rahardi, Majid (Telkomnika, 2023)
[...]we develop a conceptual model by incorporating perceived risk and trust into the technology acceptance model (TAM) theory toward the IB. IB is one of the most efficient and important types of internet commerce, experiencing significant technological advancements. Because all transactions require some level of trust, those conducted over the unreliable and impersonal nature of the internet call for substantial levels of trust due to the high level of risk frequently associated with online transactions, low levels of customer trust are frequently cited as one of the common barriers to the rapid acceptance of internet banking. Customers will perceive a higher risk and stop using the product or service in issue if they discover any discrepancy between their actual purchasing experiences and their desired purchasing outcomes. Since the majority of internet services operate in an open environment, security and privacy concerns like phishing, spoofing, malware, password, and spyware sniffing. THEORETICAL BACKGROUND Several scholars and economists analyzed the user's IB using various methods. Because there is no grounded theory in the subject of information technology (IT), academics have had to rely on models produced in other fields.